Complex Nanostructures by Pulsed Droplet Epitaxy - Noboyuki Koguchi; Sergio Bietti; Claudio Somaschini; Stefano Sanguinetti (Nanomaterials and Nanotechnology)
What makes three dimensional semiconductor quantum nanostructures so attractive is the possibility to tune their electronic properties by careful design of their size and composition. These parameters set the confinement potential of electrons and holes, thus determining the electronic and optical properties of the nanostructure. An often overlooked parameter, which has an even more relevant effect on the electronic properties of the nanostructure, is shape. Gaining a strong control over the electronic properties via shape tuning is the key to access subtle electronic design possibilities. The Pulsed Dropled Epitaxy is an innovative growth method for the fabrication of quantum nanostructures with highly designable shapes and complex morphologies. With Pulsed Dropled Epitaxy it is possible to combine different nanostructures, namely quantum dots, quantum rings and quantum disks, with tunable sizes and densities, into a single multi-function nanostructure, thus allowing an unprecedented control over electronic properties.